Inquiry-guided computer-assisted assessment and student achievement in physics - Sangga, Carolina P. (2007)
The goal of this study was determine the effects of inquiry-guided computer-assisted assessment on student achievement in physics. It delved into determining the physics achievement of students exposed to three types of computer-assisted assessment: the inquiry-guided, the adaptive, and the conventional. The sample consisted of 180 physics students enrolled during the first semester of SY 2006-07 at the Technological Institute of the Philippines, Quezon City. Physics achievement test was given to establish comparability of samples who were assigned to each computer-assisted assessment type. Inquiry-guided group got more than 50 percent of the perfect score and significantly higher than the adaptive and conventional computer assisted assessment group. The use of inquiry-guided computer-assisted assessment is therefore recommended to be used in assessment procedure.
"March 2007"
Thesis (M.A. Physics Education)--University of the Philippines Diliman.
Keywords: Physics -- Philippines -- Manila Metropolitan Area -- Computer-assisted instruction; Physics -- Examinations, questions, etc; Academic achievement -- Philippines -- Manila Metropolitan Area